Dalit Awakening and Fostering Collective Solidarity - Mohankumar B. S. (The SPL Journal of Literary Hermeneutics: A Biannual International Journal of Independent Critical Thinking, 2026)
Aim: The paper focuses on the Dalit awekening in the Telugu-speaking region taking into account social, political and literary aspects. The mainstream Indian history often misses out on Dalit resistance or the Dalit cosmos in general. Becoming conscious of their social status and economic hardships, the Dalits of the Telugu-speaking region displayed an early spirit of organization that developed alongside the Indian independence movement.Thus, to recover the lost history and to give a new understanding to the history of the marginalised is still an unfinished project. Therefore, the paper addresses this lacuna and constructs the history of Dalit awakening in Telugu speaking region. Methodology and Approach: The paper follows Dalit historiographical approach as it takes into consideration the primary and secondary texts of Dalit writers, anthologies, and research papers. The paper base itself on qualitative textual analysis. Outcome: The mainstream history and narratives often overlooks socio-political history and the literary history of Dalits and the marginalised in general. This paper throws light on the forgotten history of Dalits in Telugu speaking region as it is instrumental in fostering narratives on counter-history. Conclusion and Suggestions: History plays a vital role in construction of identities and counter-identities. Particularly, marginalised communities such as Dalits who have been struggling to recover their histories should rely on the oral and autobiographical narratives of the community. These writings from the periphery not only enriched the Telugu Dalit literature but they extended their imagination to narrate the stories of the ostracised of the ostracised.